The gnoseological limits of an economic epistemology bound in the budget of the perfect information - Villarreal, Julio Francisco (2018)
Objective: The present work provides to contrast the gnoseological effectiveness of two paradigms devoted to the study of the causes of the determination of the sovereign payment cessation by a State: those that ascribe to a voluntarist thesis of a political nature and those that understand that such a process is due to deficiencies in the provision of information. Methods: Consequently, the postulates of various schools of political economy were appealed, with special emphasis on the analysis of the causal assumptions that explain the process of sovereign default. Results: According to the conclusions of this work, the models bound in a deterministic schematism in macroeconomic matters dependent only on the availability of sufficient information for the purposes of forecasting, accounting for and interpreting the causation of a sovereign default are epistemic and heuristically deficient. Conclusions: Since both paradigms are incommensurable, it becomes reasonable and necessary the collaboration of new theoretical contributions in the matter.